The Circulation of Anti-Austerity Protest - Cammaerts, Bart (Springer International Publishing, 2018)
In this book a set of theoretical and methodological resources are presented to study the way in which protest, resistance and social movement discourses circulate through society and looks at the role of media and of communication in this process. Empirically, the focus of this book is on the UK's anti-austerity movement. 'The Circuit of Protest', as developed in this volume, is comprised of an analysis of the discourses of the anti-austerity movement and their corresponding movement frames, and the self-mediation practices geared at communicating these. The mainstream media representations and the reception of the movement discourses and frames by non-activist citizens are also studied. It is concluded that studying a movement through the prism of mediation provides a nuanced assessment in terms of failures and successes of the UK's anti-austerity movement. The book is of relevance to students and researchers of politics, social movements, as well as media and communication, but also to activists.